Dealing with a Paradigm Shift - Pack, Allan I. (J Clin Sleep Med, 2015)
Recent changes in policies by insurance companies with respect to mandating home sleep apnea testing rather than in-laboratory studies have a large impact on the financial viability of clinical sleep centers. Coping with this disruptive change requires forward planning. First, it is important to be well positioned with respect to facilities so that these can be quickly downsized to control costs. There is also a need to develop, in advance, an accredited home sleep study program so that centers can respond to the rapidly changing environment. Following the change there is a need to control costs by rapidly downsizing the technology workforce. Technologists can be retrained for other essential roles. Centralizing the precertification process with knowledgeable, well-trained staff and a robust auditing process is an essential component. The approach taken at the University of Pennsylvania to this change is described as is how one can ensure continued financial viability of a comprehensive sleep center program in a major academic medical center. CITATION: Pack AI. Dealing with a paradigm shift. J Clin Sleep Med 2015;11(8):925–929.